Traffic density independent junction-based routing in vehicular ad hoc networks - Khalid Kamal Reza Zahedi, 1980- , author; Abdul Samad Ismail; Fakulti Kejuruteraan. Sekolah Komputeran (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Doktor Falsafah (Sains Komputer)) - Universiti Teknologi Malaysia, 2018